Hubungan Paparan Alergen Asma Ditempat Kerja Dengan Keluhan Asma Di Poli Paru Instalasi Rawat Jalan Rumah Sakit Swasta Bandar Lampung Tahun 2023 - Selfianti, Selfianti; Andoko, Andoko; Furqoni, Prima Dian (Barongko: Jurnal Ilmu Kesehatan, 2023)
Asthma is a chronic inflammatory disorder of the respiratory tract that is still a serious health problem in all countries, not only in developing countries but also in developed countries. In one of the private hospitals in Kota Bandar Lampung, suspected asthma patients amounted to 84 patients in June. Known relationship between exposure to asthma allergens at work with asthma complaints at the Pulmonary Poly Outpatient Installation of Bandar Lampung Private Hospital in 2023. This research method is observational analytic with a cross-sectional research design. The location of the study was conducted at Bandar Lampung Private Hospital.The sample in this study was asthma patients with working status aged 15-65 years. Sampling is done by consecutive sampling technique. This research instrument used the ACT and SFAR questionnaires by filling out questionnaires, and data analysis using Chi Square. Based on the frequency distribution of respondents with exposure to allergens amounted to 72.6%, and respondentsn with uncontrolled asthma amounted to 76.2. Based on bivariate analysis showed that exposure to allergens with asthma complaints (p-value 0.245). Conclusion:There is no relationship between exposure to allergens at work and asthma complaints (p-value 0.245) at the Outpatient Installation Poly of Bandar Lampung Private Hospital in 2023. It is hoped that the next researcher will study more deeply about the sample with inclusion criteria not only working but housewives must also be examined because of the number of housewives who suffer asthma is quite a lot in the hospital.